Pembangunan Sistem Manajemen Proyek Berbasis Web (Studi Kasus :PT. Mitra Inti Cemerlang) - Muhammad Faris Auzan; Achmad Arwan; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Project Management that applies knowledge, skills, tools, techniques to project work activities. Poor management will impact on delays in project completion, additional costs incurred from the budget that has been prepared, the quality of construction that is not in accordance with existing requirements, and the construction process. Problems that occur at PT. Mitra Inti Cemerlang in determining material prices and labor costs, were asked to determine the price values ​​of several people who were preparing the RAB. Will cause the calculation to be wrong and can cause the contractor. Because in the process of preparing a budget plan (RAB) at PT. MIC is done by several people. In addition to the project work, a company has a project work period that must be achieved. If the contracting company cannot reach the target work time, the company will get sanctions. To assist in the process of preparing the RAB and observing the project work processes that have been carried out then to solve the problem a project management system is built. the RAB preparation process and monitoring the work processes that have been carried out. The Waterfall model will be used in the development process. And from the results of tests that have been run, this system produces valid values.